Surgical Emphysema without Pneumothorax: A Diagnostic Dilemma - Sathanantham, Dinesh Kumar; Sanganbhonia, Spurthi; Shashirekha, C. A.; Sreeramulu, P. N. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Surgical emphysema, also widely known as subcutaneous emphysema, is defined as a clinical state in which air gets trapped subcutaneously. The etiology may be traumatic or atraumatic, and multiple causes in each are present. Case report. A 63-year-old female patient presented to the emergency room with a facial soft tissue injury following road traffic accident and developed surgical emphysema later on with no evidence of rib fractures or pneumothorax. Infectious etiology was ruled out. Due to the respiratory embarrassment, the patient was electively intubated. Conservative management was provided. Emphysema resolved within 24 hours after the accident. Discussion. Various theories have been outlined in literature, like Mackler effect, Crampton theory and ballvalve mechanism. In our case, it was difficult to apply any of these theories to confirm the diagnosis. Conservative management is still used in the treatment of surgical emphysema. Conclusion. Surgical emphysema is a common encounter in trauma practice, and its identification is essential to rule out any emergency causes which may lead to respiratory distress.